Value of CD5 and CD79 in Evaluation of GIT Lymphoma - Huda Mohammed Abdulwahid; Haider AbdulRidha Alkafaji; Zainab Wehab Al Maaroof (Medical Journal of Babylon)
Background: Primary gastrointestinal lymphoma is a rare tumor, accounting for less than 5% of all GIT lymphoma, 10%–15% of all non-Hodgkin lymphoma, and encompasses 30%–40% of total extranodal lymphoma its incidence is increasing. Approximately 60%–75% of cases occur in the stomach and then small bowel, ileum. The majority of all gastrointestinal lymphoma is B cell, and T cell is less common accounting for only 6%. DLBCL and MALT lymphoma are the most histological subtypes. Expression of CD5 and CD79 aids in supporting the diagnosis of GIT lymphoma. Objective: Our study was designed to assess CD5 and CD79 overexpression in Iraqi patients with GIT lymphoma. Materials and Methods: Samples included in this study represented 30 formalin-fixed paraffin-embedded biopsy tissue blocks of patients with GIT lymphoma age from 3 to 78 years. The collected pathological blocks were related to the period 2016–2023, which was evaluated in the pathology department in Baghdad Medical City. Tissue sections were stained immunohistochemically for expression by CD5 and CD79 markers. Results: GIT lymphoma is more common in patients more than 60 years old and commonly in males. DLBCL is the most common subtype, and CD79 expression in 96.7% and CD5 expression in only 33.3 % of cases. Conclusion: CD5 expression is negative in two-thirds of patients with GIT lymphoma. CD79 is highly expressed in patients with GIT lymphoma. H score of CD79 expression has a negative correlation with age, gender, and subtypes. There is no correlation between CD79 expression and CD5 expression.